Perancangan Augmented Reality Prosedur Pembuatan Akta Kelahiran Pada Dinas Kependudukan dan Catatan Sipil Kota Medan - M. Arif Hasan; Herlina Harahap; Nur Wulan (UIN Sumatera Utara, 2022)
Currently, information for making birth certificates can only be found on the internet, information from people around and from the local population office. Researchers want to produce innovations and alternatives that are appropriate, effective and current to support the concept of information for citizens, especially on the concept of designing information media on birth certificate processing. Researchers want to produce information media that stimulates the mindset of citizens in thinking critically about problems and events that occur in their daily lives, because the nature of information media is to help them in the process of making birth certificates easily. The concept of AR on birth certificate management information produces information media that can directly provide information for making birth certificates wherever and whenever. The result of this research is an application that is run using an android smartphone that displays 3D objects when the smartphone camera is pointed at a marker.Keywords: Augmented Reality, Birth Certificate, Blender 3D, Unit